Tanggung Jawab Notaris dalam Akta Perjanjian Jual Beli Lunas Tanah dan Bangunan yang Dibuat di Hadapan Notaris (Studi Putusan Nomor 179/Pdt/2018/PT. BTN) - Rima Dian Permata (Multiverse: Open Multidisciplinary Journal, 2023)
The purpose of this research is to describe the legal responsibility of a notary in a land and building sale and purchase agreement, to describe the legal protection of buyers who have good intentions in a land and building sale and purchase agreement, how to analyze the basic legal considerations of the panel of judges in Decision Number 179/PDT/2018/ PT BTN related to the sale and purchase agreement in full for land and buildings. The research was carried out using legal research, namely normative juridical which is descriptive-analytical, which is research that aims to describe a condition or symptom or to determine whether there is a relationship between a symptom and other symptoms. The data collection technique used was a literature study. The results of the research and discussion show that the notary's legal responsibility for the sale and purchase agreement deed he made is that if the notary in making an authentic deed is not thorough and careful, then the notary can be held accountable in the form of claims to compensate for losses in the form of reimbursement of costs and compensation, because of the notary's carelessness and inaccuracy in making the deed. Legal protection for a buyer with good intentions in a sale and purchase agreement in full for land and buildings depends on the contents of the binding sale and purchase agreement (PPJB) itself. The basic analysis of the legal considerations of the panel of judges in Decision Number 179/PDT/2018/PT BTN regarding the sale and purchase agreement in full for land and buildings is that the notary has conducted research and checked and in the signing process, both the seller and the buyer have no objections, until the deed minutation process - deed made by the defendant.